A new multiaxial fatigue life prediction model for aircraft aluminum alloy. (February 2021) - Zhao, Bingfeng; Xie, Liyang; Wang, Lei; Hu, Zhiyong; Zhou, Song; Bai, Xin
Graphical abstract: Highlights: A multiaxial fatigue life prediction model is proposed for aircraft aluminum alloy. Underlying physical mechanism of nonproportional additional hardening is analysed. Subcritical plane is used to describe the particularity of nonproportional hardening. Effectiveness of the new model for aircraft aluminum alloy is verified by experiment. Abstract: Considering the frequent failure of aircraft caused by the multiaxial fatigue damage, it is very necessary to develop a reliable mathematical model to predict the multiaxial fatigue life for aircraft aluminum alloy. In our study, a new multiaxial fatigue life prediction model was proposed for both thin-walled tubular and notched specimens. In presented model, a new characteristic plane (subcritical plane) was defined to describe the particularity of additional cyclic hardening under non-proportional loading condition. On the new defined subcritical plane, a corresponding damage parameter containing the effect of additional hardening was also built, by which the dynamic path of stress spindle, combining material property and loading environment, was fully analysed. Finally, in order to verify the effectiveness of the new model for the multiaxial fatigue life prediction of aircraft aluminum alloy, multiaxial fatigue experiment for 2A12 aluminum alloy in four types of fatigue specimens was employed for the material fatigue failure simulation of the aircraft. Through the comparison result with three traditional models, it was evident the stability and accuracy of the new proposed model were much superior to those of the other three traditional models.